An efficient method for the preparation of dialkoxymethanes from dichloromethane with alcohols catalyzed by a Cu-NHC complex. Issue 36 (7th September 2016) - Zhan, Lewu; Pan, Renming; Xing, Ping; Jiang, Biao
Graphical abstract: Highlights: First report to prepare ROCH2 OR from DCM with alcohols using Cu(NHC) as catalyst. The reaction conditions are mild and the yields are excellent. The unsymmetrical ethers are also obtained using the similar method. Abstract: A facile, rapid and efficient method for the preparation of dialkoxymethanes from dichloromethane with alcohols catalyzed by a Cu-NHC complex is reported. A variety of symmetrical dialkoxymethanes can be prepared under mild condition in excellent yields (up to 98%). The unsymmetrical ether is also obtained in 89% yield from the etherification of p- tolylmethanol and n -butyl chloride catalyzed by ICyCuCl complex at 80 °C. The reaction provides a new method for the preparation of dialkoxymethanes under mild conditions in excellent yields.